(untitled) (Research, Society and Development, 2021)
The objective of the present work was to survey the main application parameters of photobiomodulation from Low-Level Light Therapy (LLLT) and / or diode therapy. light emitters (LEDT) used on FM, in addition to proposing their clinical employability through protocols that present scientific evidence. A bibliographic survey was carried out in the PUBMED databases, using the keywords available in the DESCs: "Photobiomodulation Therapy", "PBTM", "Low-Level Light Therapy", "LLLT", "Light-Emitting Diode Therapy", “LEDT","Phototherapy","Exercise","Fatigue","Performance","sport" in different combinations and associated with Boolean descriptors. The following inclusion criteria were considered: controlled and randomized clinical trials, published in English, publication period between the years 2017 to 2020 After this procedure, all abstracts were read, in which fifteen articles were selected. In the last stage, the articles were read in depth and, by applying the inclusion and exclusion criteria, only ten published articles remained. Photobiomodulation therapy performed using TLBI and LEDT is able to delay the FM process and consequently increase performance. However, the ideal application parameters of this tool still show many variables. Except for the wavelength, which is the only application parameter that shows a trend.